JURIDICAL REVIEW OF THE USE OF LETTER OF CREDIT IN ORDER TO GUARANTEE AND FACILITATE INTERNATIONAL TRADE PAYMENT TRANSACTIONS - Raspita, Desni; Apriyanto, Hendra (JILPR Journal Indonesia Law and Policy Review, 2024)
Letter of Credit (L/C) is one of the safest methods of payment in international trade from the point of view of exporters and importers. One of the purposes of using a Letter of Credit in international trade is to guarantee and expedite payments from importers by utilizing banking services. Letter of Credit (L/C) will be a bridge for exporters and importers who are separated by countries that don't know each other well. To mediate and reduce the risks of each party, the solution offered is through the Letter of Credit mechanism, which will make it easier to settle payments, secure the funds provided by the importer and risks can be transferred to the relevant bank. The type of research used in this writing is normative legal research. The data sources used are primary data sources and secondary data sources and data analysis uses qualitative analysis. The results of the research can be concluded that the payment process for import transactions uses a letter of credit (L/C), that is, when a sale and purchase agreement has been reached between the exporter and importer, then opening a letter of credit (L/C) is followed by contact with the relevant bank for delivery implementation. transaction documents and payments.